Blood of the Prodigal : An Amish Country Mystery - Gaus, Paul L. (Book collections on Project MUSE., 1999)
An Amish man exiled from his community in Ohio for fast living, returns to kidnap his son from his grandparents. Sleuth and professor Michael Branden is hired to find the boy, only to learn that the father has been murdered and the boy is missing.